Larger Than Life: The Emergent Nature of Conflict in Alaska's Upper Cook Inlet Salmon Fisheries. (30th October 2014) - Harrison, Hannah L.; Loring, Philip A.
Conflicts over natural resources are often misunderstood as being driven primarily by economic concerns or failings of human nature. However, human dimensions research has shown that conflicts are more often driven by problems and shortcomings in institutions for governance and management. In this article, we explore long-standing conflicts over the salmon fisheries of the Kenai River and Upper Cook Inlet region of Southcentral Alaska, fisheries that are embroiled in a long-standing conflict and controversy. We engaged in ethnographic research with participants from commercial, sport, and personal use fisheries in the region to understand their perceptions of these local "salmon wars." We find that these disputes are more nuanced than is captured by existing typologies of natural resource conflicts, and argue that conflicts can take on a life of their own wherein people stop responding to each other and start responding to the conflict itself, or at least the conflict as they understand it. This perspective is helpful for understanding how conflict in the region has escalated to a point of apparent dysfunction via a process known as schismogenesis. We conclude with a discussion that considers this conflict as an indicator of institutional failure from a social justice perspective, and argue that attempts for conflict management and/or resolution in cases such as these must focus first on protecting the human rights of all participants.